A study on the control indices and emission limits of substation noise. (30th March 2023) - Di, Guoqing; Jiang, Haojie; Chen, Cong; Ma, Jiangang; Wu, Jian
Highlights: Noise of substations with the voltage level of 110 kV–1000 kV was recorded. The model about L Aeq and mean noise annoyance was developed through listening tests. Control indices of noise at the boundary of substations were suggested. The limits of sound pressure level of octave bands were specified by LFNR curve. Abstract: Equivalent continuous A-weighted sound pressure level ( L Aeq ) underestimates the influence of low-frequency components of substation noise, so it is necessary to optimise control indices and emission limits of substation noise. To this end, 148 noise samples from 110 kV–1000 kV substations were selected. 280 subjects were randomly recruited for listening tests in which the 11-point numerical scale specified by ISO 15666-2021 was used. The mean noise annoyance ( A m ) of each noise sample was obtained to establish the L Aeq -A m model of substation noise. Meanwhile, the L Aeq -LFNR model was established based on the low-frequency noise rating number ( LFNR ) proposed by Broner. Based on these models, the LFNR corresponding to the limit of L Aeq could be determined. The limit of sound pressure level of substation noise was proposed at each 1/1 octave band from 31.5 Hz to 500 Hz and the limit-exceeding ratio for the existing substations noise of China was analyzed. Results showed that A m of 500 kV–1000 kV substation noise was 1.0 higher than that of 110 kV–220 kV substation noise on average when L Aeq was 25 dBA–80 dBA. L Aeq of the latter were 6.1 dBA higher than that of the former on average when A m was 1–10. It was estimated that utmost 20 % of substations need further to take noise control measures in order to meet the limit suggested by this study in China. Binding with the limit of L Aeq, the limit of sound pressure level at each octave band proposed according to equal noise annoyance can better evaluate the influence of substation noise.